MANAGEMENT OF THE PERSONNEL’S PROFESSIONAL DEVELOPMENT AT INNOVATIVELY ACTIVE ENTERPRISES - Radkevich, Valentyna (Professional Pedagogics, 2015)
The peculiarities of staff activity at innovatively active enterprises are represented in the article. It is emphasized that innovative work on its content is an intellectual activity of staff of an enterprise aimed to get the innovative product. It is clarifies that innovative work grounds new social role for the staff in the framework of innovative economics and society. The proportion of demand and offer on professions and qualifications at the innovative labour market is characterized. Offered by the government of Ukraine directions to minimize the consequences of demand and offer disproportion at the innovative labour market is outlined. The following professionally important qualities of innovative workers are theoretically grounded: innovativeness, overrepresentation of moral motivate values, the significant range of freedom and independence, self-organization and self-sufficiency, practice orientation of innovative ideas. According to the results of research on workers’ functions at innovatively active enterprises it is clarified that there is the need in development of innovative knowledge of technological processes of production job; ability to carry out the tools of technological process; keeping the technological demands to qualitative production; abidance of safety rules, abilities to practice additional qualifications; high level of culture; quality control skills, skills to solve defects and troubles of the equipment and mechanisms. To the author’s point of view it is important to develop social skills for the workers of innovatively active enterprises. They are cooperation skills, initiative skills, creative approach to professional activity, loyalty to other culture and work. It is also important to develop basic skills like achievement and transfer of information, use of ICT etc. The specific features of innovative management systems of professional staff development are shown. They are the innovative management, business-planning of innovative projects, budgeting of innovative processes....